1979
DOI: 10.1093/ajcp/71.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic Findings in Cases of Mammary Cancer Metastatic to Bone Marrow

Abstract: The hematologic findings in 22 cases of mammary cancer metastatic to bone marrow are presented. Cancer of the breast was the most frequent neoplasm metastatic in bone marrow in this study of 2,878 bone-marrow examinations. All 22 patients who had carcinoma of the breast metastatic to bone marrow had clinical, radiographic, or hematologic evidence of widespread metastatic disease. Peripheral blood was abnormal in 58% of the cases, and in most of these cases two or more abnormalities were present. Bone-marrow bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

1981
1981
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
3
1
Order By: Relevance
“…This has not been proved conclusively but considerable evidence from previous work has shown that EMA is only expressed by cells of epithelial or mesothelial derivation (Heyderman et al, 1979;Sloane & Ormerod, 1981). In the present study it was found that: (1) (Riddell & Landys, 1979;Leland & Macpherson, 1979;Ingle et al, 1978;Coombes et al, 1980). The increased diagnostic yield using trephine biopsy together with marrow aspirates has been stressed (Ingle et al, 1978;Contreras et al, 1972;Bearden et al, 1974;Leland & Macpherson, 1979;Jamshidi & Swaim, 1971;Ellis et al, 1964) but as this is at least in part due to difficulty in aspirating carcinoma cells from scirrhous tumour masses (Leland & Macpherson, 1979) it may be of less importance when attempting to detect truly micrometastatic infiltration.…”
Section: Resultscontrasting
confidence: 68%
See 1 more Smart Citation
“…This has not been proved conclusively but considerable evidence from previous work has shown that EMA is only expressed by cells of epithelial or mesothelial derivation (Heyderman et al, 1979;Sloane & Ormerod, 1981). In the present study it was found that: (1) (Riddell & Landys, 1979;Leland & Macpherson, 1979;Ingle et al, 1978;Coombes et al, 1980). The increased diagnostic yield using trephine biopsy together with marrow aspirates has been stressed (Ingle et al, 1978;Contreras et al, 1972;Bearden et al, 1974;Leland & Macpherson, 1979;Jamshidi & Swaim, 1971;Ellis et al, 1964) but as this is at least in part due to difficulty in aspirating carcinoma cells from scirrhous tumour masses (Leland & Macpherson, 1979) it may be of less importance when attempting to detect truly micrometastatic infiltration.…”
Section: Resultscontrasting
confidence: 68%
“…In the present study it was found that: (1) (Riddell & Landys, 1979;Leland & Macpherson, 1979;Ingle et al, 1978;Coombes et al, 1980). The increased diagnostic yield using trephine biopsy together with marrow aspirates has been stressed (Ingle et al, 1978;Contreras et al, 1972;Bearden et al, 1974;Leland & Macpherson, 1979;Jamshidi & Swaim, 1971;Ellis et al, 1964) but as this is at least in part due to difficulty in aspirating carcinoma cells from scirrhous tumour masses (Leland & Macpherson, 1979) it may be of less importance when attempting to detect truly micrometastatic infiltration. Our series of marrow aspirates revealed positive or suspicious cells in 19/44 (430o) of metastatic patients, but also in 3/30 (10%) of patients without conventionally demonstrable metastases at any site, including 2/20 (10%) who had primary breast carcinomas with involved axillary nodes.…”
Section: Resultsmentioning
confidence: 61%
“…Of the 37 positive cases, 6 (16.2%) had leukoerythroblastic picture with immature granulocytes and nucleated red cells in the peripheral smear. Similarly, Contreras et al [6] found leukoerythroblastic picture in 22% of their cases and Leland and MacPherson [7] in 33% of their cases. In our study, nucleated red cell and immature granulocytes were seen when the hemoglobin was reduced below 7.0% gm.…”
Section: Peripheral Bloodmentioning
confidence: 76%
“…Contreras et al [6] found leucoerythroblastic reaction in 22% of their cases and Leland and McPherson [7] in 33% of their cases. In our study, nucleated red cell and immature granulocytes were not seen in patients in whom the haemoglobin was 10% gm.…”
Section: Discussionmentioning
confidence: 89%